The last volcano : a man, a romance, and the quest to understand nature's most magnificent fury - Dvorak, John (John J.) (New York : Pegasus Books, 2015)
Documents the fifty-year career of Thomas Jaggar, the Harvard-educated volcano science pioneer who founded the Hawaiian Volcano Observatory, to share insights into his findings about massive volcanoes in such regions as Yellowstone, Alaska, and Hawaii.
Keywords: Jaggar, Thomas Augustus, -- 1871-1953; Jaggar, Thomas Augustus, -- 1871-1953; Geologists -- United States -- Biography; Volcanologists -- United States -- Biography; Volcanology -- History; Volcanoes -- Hawaii; Geologists -- United States -- Biography; Volcanologists -- United States -- Biography; Volcanoes -- History; Volcanoes -- Hawaii